The prince and the pauper - Twain, Mark (Penguin Readers, 2008)
This book set in England in 1550, is a fictional story about Prince Edward VI and Tom Canty, poor children living in the slums of London. Ten years later, they change place for a game. But then the old king dies and they cannot change back. Will the poor boy be the new King of England?